The art of fielding : a novel - Harbach, Chad. (New York : Little, Brown, 2011)
"At Westish College, a small school on the shore of Lake Michigan, baseball star Henry Skrimshander seems destined for big-league stardom. But when a routine throw goes disastrously off course, the fates of five people are upended."--from publisher's description.
Keywords: College students -- Fiction; Baseball players -- Fiction; Interpersonal relations -- Fiction; Michigan, Lake, Coast (Wis.) -- Fiction; Wisconsin -- Fiction; Psychological fiction; College stories